METHODS FOR THE ASSESSMENT OF BODY MASS INDEX IN CHILDREN AND ADULTS IN AUTOMATIC SYSTEM OF OBESITY AND OVERWEIGHT PREVENTION - A. A. Alexandrov; A. D. Deev; V. B. Rozanov; I. V. Zvezdina; E. G. Kriger (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To invent the method of body mass index (BMI) trend evaluation for children and adults for automatic system of overweight and obesity prevention. Material and methods. Into the analysis we included anthropometric data from four population-based studies, differing by the duration of observation period and age diapason. Data processing and statistical analysis were done with multidimensional regression analysis in procedure SAS PROG GLM at the variant with repeated measurements. Results. As a result of the analysis of age-related dynamics of anthropometric parameters we invented a system of BMI (increase) trend (of the Kettle index), that make it to reveal the persons (children and adults) with excessive income of BMI in its upper limits during short time intervals. This information about a child or an adult is a subject for automatic registration and is being reported to the physician. Conclusion. The proposed method makes possible to screen the persons with excessive weight gain. As a result of physician and patients' partnership it is possible to do on-time primary and secondary prevention of excessive body weight and obesity in children as in adults.